Determinan Stunting pada Anak Usia 6–24 Bulan di Puskesmas Hutaimbaru, Padang Lawas Utara - Rolanni Rizky Ashary Harahap; Razia Begum Suroyo; Yuniati Yuniati (Universitas Muhammadiyah Manado, 2025)
Stunting is a condition of long-term malnutrition that can seriously interfere with children's growth and development. Children aged 6–24 months who are stunted are at risk of brain development delays, intellectual disorders, stunted physical growth, and metabolic problems. This research was conducted in the working area of the Hutaimbaru Health Center, Halongonan District, North Padang Lawas Regency, by involving 100 stunted children under five as respondents. The method used is an analytical survey with a cross-cutting approach. Data analysis included univariate, chi-square, and logistic regression tests. The results showed that knowledge, attitudes, pregnancy checks (ANC), and husband support had a significant effect on stunting incidence. The most powerful factor is the husband's support. Mothers without partner support are 10 times more likely to have stunted children. These findings confirm the importance of the role of the family, especially the husband, in supporting the fulfillment of nutrition and optimal child care.